Indium oxide nanoparticles for resistive RAM integration using a compatible industrial technology. (February 2021) - Guenery, P.V.; León Pérez, E.A.; Ayadi, K.; Baboux, N.; Deleruyelle, D.; Blonkowski, S.; Moeyaert, J.; Baron, T.; Militaru, L.; Souifi, A.
Highlights: Uniform layer deposition by MOCVD on 12″ wafers of high density sub-10 nm indium oxide nanoparticles. Compatible CMOS BEOL process for vertical resistive memories integration. Proof-of-concept of forming-free ox-RRAM device. Bipolar resistive switching due to indium oxide nanoparticles integration. Strong Improvement of ION /IOFF ratio and retention time thanks to indium oxide NPs. Abstract: In this work we report on the integration of indium oxide (In2 O3 ) nanoparticles (NPs) for Resistive Random Access Memory (RRAM) applications. This low-temperature integration process is fully compatible CMOS Back-End integration given a carefull selection of materials deposited by MOCVD and ALD. A detailed description of the process is provided together with AFM analysis performed on the indium oxide nanoparticles and TEM cross-sections on the whole stack. It is shown that the introduction of In2 O3 NPs provides bipolar switching behavior together with promising electrical performances in terms of large OFF/ON resistance ratio (10 6 ) and retention time at room temperature.